Antioxidant effect of minocycline in gingival epithelium induced by Actinobacillus actinomycetemcomitans serotype B toxin - Ernie Maduratna Setiawati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2009)
Background: Actinobacillus actinomycetemcomitans (Aa) serotype B has been associated with aggressive periodontitis. Gingival epithelial cell is exquisitely sensitive to the toxin and may lead to the epithel protective barrier disruption. Experimental models show that minocycline is not related to it’s antimicrobial effect and protection against neuron cell apoptosis of a number experimental models of brain injury and Parkinson’s disease. Purpose: This study, examined antioxidant effect of minocycline to inhibit apoptosis of gingival epithelium induced crude toxin bacteria Aa serotype B in mice. Methods: Thirty adult mice strain Swiss Webster (balb C) were divided randomly into three groups: control group (group A), toxin group (group B) and toxin and minocycline group (group C). The mice were taken at 24 hours after application, and then the tissue sections of gingival epithelium were stained with tunnel assay and immunohistochemistry. Result: Treatment with these toxin induced apoptosis of gingival epithelium and was associated with DNA fragmentation and reduced gluthatione (GSH). Minocycline 100 nM significantly increased GSH and reduced apoptosis (p < 0.05). Minocycline provides antioxidant effect against citotoxicity of bacteria Aa serotipe B. Conclusion: Nanomolar concentration of minocycline potential as new therapeutic agent to prevent progressivity of aggressiveness of periodontitis.